A high-performance fireproof cable with composite mica copper sheath for high-speed railway
By using modified composite fillers and flame retardant additives in the sheath layer material of cables for high-speed rail, the problem that cables are prone to high-temperature softening and fire in high-temperature environments is solved, and excellent thermal oxygen aging and flame retardant are achieved. and heat resistance, improving the safety of cable use.
Patent Information
- Application Number
- CN202411502667.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-10-25
AI Technical Summary
High-speed rail cables are prone to high-temperature softening and fire damage in high-temperature environments. The existing cables lack heat resistance and fire resistance, making it difficult to effectively protect the core wire and prevent the spread of fire.
Using modified composite fillers and flame retardant additives, the aminolated mica powder and graphene oxide are grafted through chemical reactions and grafted with crosslinking intermediates to prepare excellent heat-oxygen aging resistance, flame retardant and heat resistance. Performance sheathing layer material.
It improves the thermal oxygen aging resistance, flame retardancy and heat resistance of the cable, enhances the fire resistance of the cable, effectively protects the core wire and prevents the spread of the fire, and improves the safety of the cable use.
Smart Images

Figure CN118994768B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fireproof cables, and in particular relates to a composite mica copper sheathed high-performance fireproof cable for high-speed railways. Background Art
[0002] The operation and laying environment of high-speed rail cables is complex. During operation, the high-speed rail has high locomotive power and long high-speed operation time, which causes the local temperature to rise sharply. In addition, some cables need to work in a high-temperature environment for a long time in summer. On the one hand, long-term work in a high-temperature environment will cause the high-temperature softening of the cable. On the other hand, high temperature is also prone to cause fire, reducing the safety of places around the cable. This puts more stringent requirements on the heat resistance and fire resistance of the cable. As the first layer of barrier for power cables, the sheath layer should be made of materials with good heat resistance and flame retardancy to play a protective role.
[0003] A Chinese patent with application number CN201611207458.X discloses a halogen-free, low-smoke, flame-retardant power cable for nuclear power plants. The cable is made of a composite of dolomite powder, granite powder, attapulgite, zeolite powder and mica powder as a flame-retardant filler, and the core wire is wrapped with the flame-retardant filler, so that the prepared power cable has good halogen-free, low-smoke, flame-retardant properties. However, after the core wire is wrapped with a large amount of stone powder and clay, the heat generated by the power transmission is difficult to release to the outside. In the long run, the outer insulation layer of the core wire will age and lose its effectiveness, seriously affecting the long-distance power transmission effect of the power cable. Moreover, as the outermost sheath layer, the flame retardant properties are not effectively improved. Once a fire occurs, it is difficult to prevent the fire from spreading.
[0004] In summary, there is an urgent need to provide a sheath layer with excellent thermal oxygen aging resistance, flame retardancy and heat resistance, which is of great significance to improving the safety of cable use. Summary of the invention
[0005] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a high-performance fire-resistant cable with a composite mica copper sheath for high-speed railways. By adding modified composite fillers and flame retardant additives, the cable sheath layer material is endowed with excellent heat-oxidation aging resistance, flame retardancy and heat resistance.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A composite mica copper sheathed high-performance fireproof cable for high-speed railways, comprising a plurality of insulating cores, an inorganic tape, a copper sheath, and a sheath layer arranged in sequence from the inside to the outside, wherein the insulating core comprises a copper conductor and a mica tape insulation layer wrapped around the surface of the copper conductor, and a mineral material is filled between the mica tape insulation layer and the inorganic tape;
[0008] The sheath layer is prepared by pulling the sheath layer material out of the copper sheath through an extrusion device; the sheath layer material includes the following raw materials in parts by weight: 70-90 parts of low-density polyethylene, 10-15 parts of ethylene-tetrafluoroethylene copolymer, 5-10 parts of modified composite filler, 2-5 parts of flame retardant additive, 3-4 parts of diisopropylbenzene peroxide, 2-2.5 parts of triallyl isocyanurate, 1-2 parts of plasticizer, and 0.1-0.3 parts of lubricant;
[0009] The modified composite filler is prepared by grafting amino mica powder and graphene oxide by chemical reaction and then further grafting with a cross-linking intermediate, wherein the cross-linking intermediate is prepared by treating triallyl isocyanurate with 3-mercaptopropyltrimethoxysilane to produce a mercapto-double bond Michael addition reaction; the flame retardant additive is prepared by grafting hexachlorocyclotriphosphazene and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide by chemical reaction and then polymerizing them with p-phenylenediamine as a linker.
[0010] Preferably, the mineral material is a mixture of kaolin, magnesium oxide and calcium oxide in a mass ratio of 50:10-20:10-20.
[0011] Preferably, the plasticizer is any one of dimethyl phthalate, dioctyl phthalate and diisodecyl phthalate; and the lubricant is polyethylene wax.
[0012] Preferably, the method for preparing the flame retardant additive comprises the following steps:
[0013] A. Hexachlorocyclotriphosphazene is placed in a reactor filled with acetonitrile solvent, and the temperature is raised to 45-60° C. 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is dissolved in acetonitrile and then added to the reactor for mixing, and triethylamine solution is slowly added dropwise, and the reaction is carried out for 10-12 hours. After the reaction is completed, the product is filtered, washed, and dried to obtain a flame retardant primary product;
[0014] B. Dissolve p-phenylenediamine in acetonitrile and disperse by ultrasonic to obtain solution 1. Dissolve the initial flame retardant product in acetonitrile and disperse by ultrasonic to obtain solution 2. Transfer solution 1 to a reactor, add solution 2 and triethylamine, and reflux at 75-90°C for 20-24h. After the reaction is completed, filter, wash and dry to obtain a flame retardant additive.
[0015] Preferably, in step A, the molar ratio of hexachlorocyclotriphosphazene to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:3-3.2.
[0016] Preferably, in step B, the molar ratio of p-phenylenediamine to the flame retardant primary product is 1.6-1.75:1-1.2.
[0017] Preferably, the method for preparing the modified composite filler comprises the following steps:
[0018] (1) γ-aminopropyltriethoxysilane, deionized water and anhydrous ethanol are mixed evenly to obtain a silane hydrolyzate, mica powder and anhydrous ethanol are placed in a reactor, the silane hydrolyzate is added, the temperature is raised to 60-70° C. and the mixture is kept evenly mixed under a nitrogen atmosphere for reaction for 5-7 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain amino mica powder;
[0019] (2) ultrasonically dispersing graphene oxide in deionized water, adding amino mica powder, adjusting the pH value of the system to 7-9 with sodium carbonate solution, then adding carbodiimide and N-hydroxysuccinimide and stirring to react for 4-6 hours. After the reaction is completed, filtering and drying are performed to prepare a composite filler;
[0020] (3) taking triallyl isocyanurate and dichloromethane into a reactor, taking 3-mercaptopropyltrimethoxysilane, triethylamine and dichloromethane and stirring them evenly, and then adding them into the reactor, reacting for 18 to 20 hours under a nitrogen atmosphere to prepare a cross-linked intermediate;
[0021] (4) The composite filler is placed in a reactor, and a mixed solution of anhydrous ethanol and deionized water is added and ultrasonically dispersed uniformly. The pH value of the system is adjusted to 3-5, and a cross-linking intermediate is added. The temperature is raised to 60-75°C and the mixture is kept uniformly mixed and reacted under a nitrogen atmosphere for 7-8 hours. After the reaction is completed, the modified composite filler is prepared by filtering, washing, and drying.
[0022] Preferably, in step (3), the mass ratio of triallyl isocyanurate to 3-mercaptopropyltrimethoxysilane is 1.7-2.2:1.
[0023] Preferably, in step (4), the addition ratio of the composite filler to the cross-linked intermediate is 5-6.5 g: 10-15 mL.
[0024] Preferably, the method for preparing the sheath layer material comprises the following steps:
[0025] S1, adding parts by weight of low-density polyethylene, ethylene-tetrafluoroethylene copolymer, modified composite filler, flame retardant additive, plasticizer and lubricant into a mixer, mixing for 5-7 minutes, adding parts by weight of diisopropylbenzene peroxide and triallyl isocyanurate, mixing for 8-15 minutes to prepare a mixture;
[0026] S2. The obtained mixture is melted at 120-125° C. for 5-7 min using a flat vulcanizer, and then subjected to a cross-linking reaction at 170-180° C. and 14-16 MPa for 25-30 min to prepare a sheath layer material.
[0027] Beneficial effects of the present invention:
[0028] The invention uses hexachlorocyclotriphosphazene, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and p-phenylenediamine as raw materials, acetonitrile as solvent, triethylamine as acid binding agent, replaces three chlorine atoms on hexachlorocyclotriphosphazene with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and then uses p-phenylenediamine as a linker to replace the remaining chlorine atoms on hexachlorocyclotriphosphazene to prepare a flame retardant additive. The flame retardant additive structure contains a large number of P=O, PO and P=N groups, and a large number of PO∙ and HPO∙ free radicals will be generated during combustion, which can achieve excellent flame retardant effect. At the same time, the introduction of the antioxidant p-phenylenediamine produces multiple anti-aging functional groups -NH, which enhances the aging protection effect of the cable material.
[0029] The present invention utilizes amino mica powder and graphene oxide to undergo a covalent reaction under the action of a carboxyl activator to form a composite filler connected by amide bonds, thereby reducing the oxygen content in graphene oxide and improving its heat resistance, and also improving the mechanical properties, electrical insulation properties and thermal stability of the composite material. At the same time, the present invention utilizes 3-mercaptopropyltrimethoxysilane to treat the crosslinking agent triallyl isocyanurate to undergo a mercapto-double bond Michael addition reaction to prepare a crosslinking intermediate, and then the crosslinking intermediate is grafted with the composite filler to prepare a modified composite filler. The diisopropyl peroxide added in the present invention triggers low-density polyethylene macromolecules to form free radicals, and under the action of high temperature, the double bonds in the modified composite filler are broken, and the formed free radicals are combined with the free radicals formed by the low-density polyethylene at high temperature, and the modified composite filler is grafted into the three-dimensional network structure of the crosslinked polyethylene macromolecule chain, thereby achieving the enhancement of the strength and heat resistance of the modified composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0031] Figure 1 It is a structural schematic diagram of the composite mica copper sheathed high-performance fireproof cable for high-speed railway of the present invention.
[0032] In the figure: 1-insulated core, 11-copper conductor, 12-mica tape insulation layer, 2-mineral material, 3-inorganic tape, 4-copper sheath, 5-sheath layer. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] like Figure 1 As shown, a composite mica copper sheathed high-performance fire-proof cable for high-speed railways is provided with a plurality of insulating cores 1, inorganic tapes 3, copper sheaths 4, and sheath layers 5 in sequence from the inside to the outside, wherein the insulating core 1 comprises a copper conductor 11 and a mica tape insulation layer 12 wrapped around the surface of the copper conductor 11, and a mineral material 2 is filled between the mica tape insulation layer 12 and the inorganic tape 3.
[0035] Example 1 A method for preparing a flame retardant additive comprises the following steps:
[0036] A. Take 3.48g of hexachlorocyclotriphosphazene and put it into a reactor containing 50mL of acetonitrile solvent, heat it to 50°C, take 6.52g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, add 100mL of acetonitrile to dissolve it, add it to the reactor and mix it, slowly add 3mL of triethylamine solution, react for 12h, filter, wash and dry it after the reaction is completed to prepare a flame retardant primary product;
[0037] B. Take 0.37g of p-phenylenediamine and dissolve it in 30mL of acetonitrile, and disperse it by ultrasonic to obtain solution 1. Take 0.9g of the flame retardant primary product and dissolve it in 70mL of acetonitrile, and disperse it by ultrasonic to obtain solution 2. Move solution 1 to a reactor, add solution 2 and 3.5mL of triethylamine, and place it under reflux at 85°C for 24h. After the reaction is completed, filter, wash and dry to prepare a flame retardant additive.
[0038] Example 2 A method for preparing a modified composite filler comprises the following steps:
[0039] (1) Take 20 mL of γ-aminopropyltriethoxysilane, 10 mL of deionized water and 70 mL of anhydrous ethanol and mix them evenly to obtain a silane hydrolyzate, take 5 g of mica powder and 5 mL of anhydrous ethanol in a reactor, add the silane hydrolyzate, heat to 65 ° C and keep the mixture evenly mixed under a nitrogen atmosphere for 5 hours, and after the reaction is completed, filter, wash and dry to prepare amino mica powder;
[0040] (2) 2 g of graphene oxide was ultrasonically dispersed in 250 mL of deionized water, 4 g of amino mica powder was added, the pH value of the system was adjusted to 8 using a 10% sodium carbonate solution, and then 0.02 g of carbodiimide and 0.03 g of N-hydroxysuccinimide were added and stirred for 6 h. After the reaction was completed, the composite filler was prepared by filtration and drying;
[0041] (3) 6.5 g of triallyl isocyanurate and 10 mL of dichloromethane were placed in a reactor, 3 g of 3-mercaptopropyltrimethoxysilane, 0.3 g of triethylamine and 6 mL of dichloromethane were mixed evenly, and then added to the reactor, and reacted for 18 hours under a nitrogen atmosphere to prepare a cross-linked intermediate;
[0042] (4) 5.8 g of the composite filler was placed in a reactor, and a mixed solution of 80 mL of anhydrous ethanol and 20 mL of deionized water was added for uniform ultrasonic dispersion. The pH value of the system was adjusted to 4, and 12 mL of the cross-linked intermediate was added. The temperature was raised to 70 °C and the mixture was kept uniformly mixed under a nitrogen atmosphere for 8 h. After the reaction was completed, the modified composite filler was prepared by filtration, washing, and drying.
[0043] Example 3 A sheath layer material includes the following raw materials in parts by weight:
[0044] 72 parts of low-density polyethylene, 10 parts of ethylene-tetrafluoroethylene copolymer, 5 parts of modified composite filler prepared in Example 2, 2 parts of flame retardant additive prepared in Example 1, 3 parts of diisopropylbenzene peroxide, 2 parts of triallyl isocyanurate, 1 part of plasticizer dimethyl phthalate, and 0.1 part of lubricant polyethylene wax.
[0045] The method for preparing the above-mentioned sheath layer material comprises the following steps:
[0046] S1, adding parts by weight of low-density polyethylene, ethylene-tetrafluoroethylene copolymer, modified composite filler, flame retardant additive, plasticizer and lubricant into a mixer, mixing for 5 minutes, adding parts by weight of diisopropylbenzene peroxide and triallyl isocyanurate, mixing for 10 minutes to prepare a mixture;
[0047] S2. The obtained mixture is melted at 120° C. for 5 min using a flat vulcanizer, and then subjected to a cross-linking reaction at 175° C. and 15 MPa for 30 min to prepare a sheath layer material.
[0048] Example 4 A sheath layer material includes the following raw materials in parts by weight:
[0049] 81 parts of low-density polyethylene, 12 parts of ethylene-tetrafluoroethylene copolymer, 7 parts of modified composite filler prepared in Example 2, 3 parts of flame retardant additive prepared in Example 1, 3 parts of diisopropylbenzene peroxide, 2 parts of triallyl isocyanurate, 1 part of plasticizer dimethyl phthalate, and 0.2 parts of lubricant polyethylene wax.
[0050] The preparation method of the above-mentioned sheath layer material is the same as that of Example 3.
[0051] Example 5 A sheath layer material includes the following raw materials in parts by weight:
[0052] 90 parts of low-density polyethylene, 15 parts of ethylene-tetrafluoroethylene copolymer, 10 parts of the modified composite filler prepared in Example 2, 5 parts of the flame retardant additive prepared in Example 1, 4 parts of diisopropylbenzene peroxide, 2.5 parts of triallyl isocyanurate, 2 parts of plasticizer dimethyl phthalate, and 0.3 parts of lubricant polyethylene wax.
[0053] The preparation method of the above-mentioned sheath layer material is the same as that of Example 3.
[0054] Comparative Example 1 A method for preparing a flame retardant additive comprises the following steps:
[0055] Take 3.48g of hexachlorocyclotriphosphazene and put it into a reactor filled with 50mL of acetonitrile solvent, heat it to 50°C, take 6.52g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, add 100mL of acetonitrile to dissolve it, then add it to the reactor and mix it, slowly add 3mL of triethylamine solution, react for 12h, and after the reaction is completed, filter, wash and dry it to prepare a flame retardant additive.
[0056] Comparative Example 2 A method for preparing a composite filler comprises the following steps:
[0057] (1) Take 20 mL of γ-aminopropyltriethoxysilane, 10 mL of deionized water and 70 mL of anhydrous ethanol and mix them evenly to obtain a silane hydrolyzate, take 5 g of mica powder and 5 mL of anhydrous ethanol in a reactor, add the silane hydrolyzate, heat to 65 ° C and keep the mixture evenly mixed under a nitrogen atmosphere for 5 hours, and after the reaction is completed, filter, wash and dry to prepare amino mica powder;
[0058] (2) Take 2 g of graphene oxide and ultrasonically disperse it in 250 mL of deionized water, add 4 g of amino mica powder, use 10% sodium carbonate solution to adjust the pH value of the system to 8, then add 0.02 g of carbodiimide and 0.03 g of N-hydroxysuccinimide and stir to react for 6 h. After the reaction is completed, filter and dry to prepare a composite filler.
[0059] Comparative Example 3 A sheath layer material includes the following raw materials in parts by weight:
[0060] 90 parts of low-density polyethylene, 15 parts of ethylene-tetrafluoroethylene copolymer, 10 parts of modified composite filler prepared in Example 2, 5 parts of flame retardant additive prepared in Comparative Example 1, 4 parts of diisopropylbenzene peroxide, 2.5 parts of triallyl isocyanurate, 2 parts of plasticizer dimethyl phthalate, and 0.3 parts of lubricant polyethylene wax.
[0061] The preparation method of the above-mentioned sheath layer material is the same as that of Example 3.
[0062] Comparative Example 4 A sheath layer material includes the following raw materials in parts by weight:
[0063] 90 parts of low-density polyethylene, 15 parts of ethylene-tetrafluoroethylene copolymer, 10 parts of the composite filler prepared in Comparative Example 2, 5 parts of the flame retardant additive prepared in Example 1, 4 parts of diisopropylbenzene peroxide, 2.5 parts of triallyl isocyanurate, 2 parts of plasticizer dimethyl phthalate, and 0.3 parts of lubricant polyethylene wax.
[0064] The preparation method of the above-mentioned sheath layer material is the same as that of Example 3.
[0065] Comparative Example 5 A sheath layer material includes the following raw materials in parts by weight:
[0066] 90 parts of low-density polyethylene, 15 parts of ethylene-tetrafluoroethylene copolymer, 7 parts of mica powder, 3 parts of graphene oxide, 5 parts of the flame retardant additive prepared in Example 1, 4 parts of diisopropylbenzene peroxide, 2.5 parts of triallyl isocyanurate, 2 parts of plasticizer dimethyl phthalate, and 0.3 parts of lubricant polyethylene wax.
[0067] The preparation method of the above-mentioned sheath layer material is the same as that of Example 3.
[0068] Performance Testing
[0069] (1) Flame retardant performance test: The sheath layer materials prepared in Examples 3-5 and Comparative Examples 3-5 were made into test samples with a specification of 100 mm×6.5 mm×3 mm. The flame retardant performance of the samples was evaluated by referring to the limiting oxygen index of the test samples in accordance with GB / T 2406.2-2009. Generally speaking, the larger the limiting oxygen index, the better the flame retardant performance, and vice versa. The data results are shown in Table 1.
[0070] Table 1 Test results of flame retardant properties of samples
[0071]
[0072] It can be seen from the data in Table 1 that the sheath layer materials prepared in Examples 3-5 of the present invention have a high limiting oxygen index and excellent flame retardant properties. In Comparative Example 3, p-phenylenediamine is not used as a linker, and the flame retardant properties measured are significantly lower than those of Examples 3-5. The reason is that p-phenylenediamine can be used as a linker for the polymerization of flame retardant primary products, which is beneficial to improving the flame retardant properties of the material.
[0073] (2) Mechanical properties and heat resistance test: The sheath layer materials prepared in Example 3-5 and Comparative Example 3-5 were subjected to a tensile property test according to GB / T 1040.2-2022, and the change rates of tensile strength and elongation at break were tested after aging at 110°C for 168h. The sample strip size was 100mm×5mm×3.5mm. The sheath layer materials prepared in Example 3-5 and Comparative Example 3-5 were placed in a TGA-103 thermogravimetric analyzer, respectively. Under nitrogen protection, the temperature was increased from room temperature to 800°C at a heating rate of 5°C / min. The initial decomposition temperature of the material was recorded and its heat resistance was evaluated. Generally speaking, the higher the initial decomposition temperature, the stronger the heat resistance, and vice versa. The data results are shown in Table 2.
[0074] Table 2 Test results of mechanical properties and heat resistance of samples
[0075]
[0076] From the data in Table 2, it can be seen that the sheath layer material prepared in Examples 3-5 of the present invention has the characteristics of high tensile strength, not easy to break, and high initial decomposition temperature, and has good heat resistance. Among them, in Comparative Example 3, p-phenylenediamine is not used as a linker, and the tensile strength change rate and elongation at break change rate measured are significantly changed compared with Examples 3-5, because the antioxidant p-phenylenediamine is not introduced into the structure of the flame retardant additive. In Comparative Example 4, the cross-linked intermediate is not grafted with the composite filler, and the tensile strength and elongation at break measured are slightly lower than those of Examples 3-5, and the initial decomposition temperature is significantly lower than that of Examples 3-5, which may be due to the fact that the composite filler is not grafted into the three-dimensional network structure of the cross-linked polyethylene macromolecular chain. In Comparative Example 5, mica powder and graphene oxide are simply mixed, and the tensile strength and elongation at break measured are worse than those of Examples 3-5, which may be due to the agglomeration phenomenon that reduces its mechanical properties, and the initial decomposition temperature is slightly lower than that of Examples 3-5, because the oxygen content in graphene oxide reduces its heat resistance.
[0077] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A high-performance fireproof cable with composite mica copper sheath for high-speed railway, characterized in that: It includes a plurality of insulating wire cores, an inorganic tape, a copper sheath, and a sheath layer arranged in sequence from the inside to the outside, wherein the insulating wire core includes a copper conductor and a mica tape insulating layer wrapped around the surface of the copper conductor, and a mineral material is filled between the mica tape insulating layer and the inorganic tape; The sheath layer is prepared by pulling the sheath layer material out of the copper sheath through an extrusion device; the sheath layer material includes the following raw materials in parts by weight: 70-90 parts of low-density polyethylene, 10-15 parts of ethylene-tetrafluoroethylene copolymer, 5-10 parts of modified composite filler, 2-5 parts of flame retardant additive, 3-4 parts of diisopropylbenzene peroxide, 2-2.5 parts of triallyl isocyanurate, 1-2 parts of plasticizer, and 0.1-0.3 parts of lubricant; The modified composite filler is prepared by grafting amino mica powder and graphene oxide by chemical reaction and then further grafting with a cross-linking intermediate, wherein the cross-linking intermediate is prepared by treating triallyl isocyanurate with 3-mercaptopropyltrimethoxysilane to undergo a mercapto-double bond Michael addition reaction; the flame retardant additive is prepared by grafting hexachlorocyclotriphosphazene and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide by chemical reaction and then polymerizing them with p-phenylenediamine as a linker; The preparation method of the flame retardant additive comprises the following steps: A. Hexachlorocyclotriphosphazene is placed in a reactor filled with acetonitrile solvent, and the temperature is raised to 45-60° C. 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is dissolved in acetonitrile and then added to the reactor for mixing, and triethylamine solution is slowly added dropwise, and the reaction is carried out for 10-12 hours. After the reaction is completed, the product is filtered, washed, and dried to obtain a flame retardant primary product; B. Dissolve p-phenylenediamine in acetonitrile and disperse by ultrasonic to obtain solution 1; dissolve the flame retardant primary product in acetonitrile and disperse by ultrasonic to obtain solution 2; transfer solution 1 to a reactor, add solution 2 and triethylamine, and reflux at 75-90° C. for 20-24 hours. After the reaction is completed, filter, wash and dry to obtain a flame retardant additive; The preparation method of the modified composite filler comprises the following steps: (1) γ-aminopropyltriethoxysilane, deionized water and anhydrous ethanol are mixed evenly to obtain a silane hydrolyzate, mica powder and anhydrous ethanol are placed in a reactor, the silane hydrolyzate is added, the temperature is raised to 60-70° C. and the mixture is kept evenly mixed under a nitrogen atmosphere for reaction for 5-7 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain amino mica powder; (2) ultrasonically dispersing graphene oxide in deionized water, adding amino mica powder, adjusting the pH value of the system to 7-9 with sodium carbonate solution, then adding carbodiimide and N-hydroxysuccinimide and stirring to react for 4-6 hours. After the reaction is completed, filtering and drying are performed to prepare a composite filler; (3) taking triallyl isocyanurate and dichloromethane into a reactor, taking 3-mercaptopropyltrimethoxysilane, triethylamine and dichloromethane and stirring them evenly, and then adding them into the reactor, reacting for 18 to 20 hours under a nitrogen atmosphere to prepare a cross-linked intermediate; (4) The composite filler is placed in a reactor, and a mixed solution of anhydrous ethanol and deionized water is added and ultrasonically dispersed uniformly. The pH value of the system is adjusted to 3-5, and a cross-linking intermediate is added. The temperature is raised to 60-75°C and the mixture is kept uniformly mixed and reacted under a nitrogen atmosphere for 7-8 hours. After the reaction is completed, the modified composite filler is prepared by filtering, washing, and drying.
2. The high-speed rail composite mica copper sheathed high-performance fireproof cable according to claim 1 is characterized in that: The mineral material is prepared by mixing kaolin, magnesium oxide and calcium oxide in a mass ratio of 50:10-20:10-20.
3. The high-speed rail composite mica copper sheathed high-performance fireproof cable according to claim 1 is characterized in that: The plasticizer is any one of dimethyl phthalate, dioctyl phthalate and diisodecyl phthalate; and the lubricant is polyethylene wax.
4. The high-speed railway composite mica copper sheathed high-performance fireproof cable according to claim 1, characterized in that: In the step A, the molar ratio of hexachlorocyclotriphosphazene to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:3-3.
2.
5. The high-speed railway composite mica copper sheathed high-performance fireproof cable according to claim 1, characterized in that: In the step B, the molar ratio of p-phenylenediamine to the flame retardant primary product is 1.6-1.75:1-1.
2.
6. The high-speed railway composite mica copper sheathed high-performance fireproof cable according to claim 1, characterized in that: In the step (3), the mass ratio of triallyl isocyanurate to 3-mercaptopropyltrimethoxysilane is 1.7-2.2:
1.
7. The high-speed railway composite mica copper sheathed high-performance fireproof cable according to claim 1, characterized in that: In the step (4), the addition ratio of the composite filler to the cross-linked intermediate is 5-6.5 g: 10-15 mL.
8. The high-speed railway composite mica copper sheathed high-performance fireproof cable according to claim 1, characterized in that: The preparation method of the sheath layer material comprises the following steps: S1, adding parts by weight of low-density polyethylene, ethylene-tetrafluoroethylene copolymer, modified composite filler, flame retardant additive, plasticizer and lubricant into a mixer, mixing for 5-7 minutes, adding parts by weight of diisopropylbenzene peroxide and triallyl isocyanurate, mixing for 8-15 minutes to prepare a mixture; S2. The obtained mixture is melted at 120-125° C. for 5-7 min using a flat vulcanizer, and then subjected to a cross-linking reaction at 170-180° C. and 14-16 MPa for 25-30 min to prepare a sheath layer material.
Citation Information
Patent Citations
Halogen-free low-smoke flame-retardant power cable for nuclear power station
CN106782855A
Halogen-free sulphonic acid ester and / or sulphinic acid ester as flame retardant, flame retardant synergists and radical generators in plastics
CN110945066A
Nitrogen-phosphorus synergistic ionic flame retardant as well as preparation method and application thereof
CN115160371A
Cited By
Multi-layer composite nano-doped high-flame-retardant insulating film material and preparation method thereof
CN121718254A
Dust-free high-flexibility cable sheath
CN224190705U